Absattar Derbisali and kazakh oriental studies. (Journal of Oriental Studies, 2016)
This article submit an analysis of scientific works of the famous scientist and one of the founders of Kazakh Oriental Studies Absattar kazhy Derbіsalі . And also investigated scientific values such as his monograph “Arab adebietі “, “Arabic-language literature of Morocco” and fundamental work such worksas “ Shynyrau bulaktar “, “Kazak dalasynyn zhuldyzdary” and etc.
Keywords: Arab literature; literary connections; Islam; oriental studies; spiritual heritage